Estimation and validation of acenocoumarol dosing algorithms in Bulgarian patients with cardiovascular diseases. (June 2015) - Tzveova, Reni; Dimitrova-Karamfilova, Antoaneta; Saraeva, Radoslava; Solarova, Tanya; Naydenova, Galya; Petrova, Irina; Hristova, Nataliya; Popov, Ivan; Nachev, Gencho; Mitev, Vanio; Kaneva, Radka
Aim & Methods: A total of 169 Bulgarian patients were genotyped for CYP2C9*2, *3, VKORC1-1639G>A and VKORC11173C>T . The effect of genetic and nongenetic factors on acenocoumarol dose variability was tested in a derivation cohort of patients and the obtained algorithm was validated in a test cohort.Results & Discussion: It was found that VKORC-1639G>A (25.5%), CYP2C9*2 (7.8%), CYP2C9*3 (6.1%), age (13.6%) and diagnosis (6.0%) significantly affected acenocoumarol dose variability in the derivation cohort. These factors with additional factors, such as sex (0.1%, p = 0.76), weight (2.6%, p = 0.14) and amiodarone use (3.0%, p = 0.059) accounted for 46.5% and 23.0% of the dose variability for genetic and clinical models, respectively.Conclusion: Based on the results of this investigation, validated clinical and pharmacogenetic algorithms for the prediction of a stable anticoagulant dose were developed, specifically designed for the Bulgarian population.